Relationship between psycho-maturity and performance of sepak takraw - Rabiu Muazu, Musa; Anwar, P. P. Abdul Majeed; Norlaila Azura, Kosni; Mohamad Razali, Abdullah (Springer, 2020)
The correlation between psycho-maturity towards the performance of sepak takraw players is evaluated in this chapter. The Louvain clustering algorithm is used to categorise the players to high, medium and low psycho-matured players based on seven fundamental psychological measures, viz. maturity status, selftalk, activation, imagery, emotion control, automaticity and goal setting. Different random forest classifiers were developed to classify the players based on the aforesaid psychological measures. It was shown that the optimised model could provide reasonable discrimination between the players with a classification accuracy of 82.61% on the test dataset, suggesting the significance of the psychological indicators towards the performance of the players.